Managing children’s services in the public library - Fasick, Adele M (Libraries Unlimited, 2008)
This edition is organized into four major content areas: planning services for children in the context of a community; managing the department, which includes recruiting and retaining staff, communicating with colleagues, annual reports, budgeting, and security; managing services—including collection development, electronic resources, intellectual freedom, and outreach; and professional development. All of the sections have been updated to include new and relevant information especially in relation to technological advances and challenges